Mapping the Fourfold Gospel: Textual Geography in the Eusebian Apparatus - Coogan, Jeremiah (Journal of early Christian studies, 2017)
Eusebius of Caesarea (ca. 260-339 c.e.) invented a paratextual apparatus for reading Matthew, Mark, Luke, and John as a fourfold unity. Yet despite Eusebius's creativity and the long afterlife of his invention, the apparatus remains underappreciated and widely misunderstood. This article argues that Michel de Certeau's distinction between itineraries and maps illuminates the innovative function of the Eusebian apparatus, which contrasts with earlier attempts at gospel harmony and synopsis. Instead of disrupting the narrative integrity of the four canonical gospels, Eusebius's map creates a canonical space that preserves gospel narrative and facilitates exegetical and liturgical appropriation.